The Characteristics of treated Matang fibrous peat in drained and undrained triaxial compression tests - Hwa, Jacqueline Lam Wan (Universiti Malaysia Sarawak (UNIMAS), 2012)
peat soil is well known as problematic soil due to their high water content, high compressibility and low shear strength. The chosen study area is Matang, Kuching, Sarawak, an upcoming development in the state with mushrooming housing estates and commercial centers. Studies have been carried out on preliminary tests on the untreated peat and strength evaluation of stabilized tropical fibrous peat samples The stabilizing agent used was Ordinary Portland Cement (OPC) due to its high strength and availability. Remolded cemented peat samples were prepared with cement content of 10%, 25% and 50% by weight of dry soil and cured for 7, 14, 28 and 90 days. These stabilized samples were tested for their strength through unconfin$j1 compression (UC), unconsolidated undrained (UU), isotropic consolidated undrained (CIU) and isotropic consolidated drained (CID) triaxial compression tests. From these tests, it was found that as the addition of cement to soil and curing period increased, soil's stiffness and strength increased in the UC, UU and CID tests but to a certain limit in the CIU tests. It was also found that the UU test results were found to be linearly proportional to UC tests with R-square of above 0.974. The friction angle of cement stabilized peat samples was higher than untreated peat but the observed trend was not meaningful for longer curing time and higher cement content due to the small changes. CD test results are more reliable in comparison to CU test because it idealizes the soil behavior in the real condition, but this test takes longer period to perfonn. Thus, a reduction factor for the effective friction angle of cement stabilized peat that was obtained in CIU and CID tests was in the range of 0.81 to 0.97. The strength behavior of the cement stabilized peat is affected by cement content, curing time, moisture content and confining pressure.